2016
DOI: 10.1152/ajprenal.00226.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific regulation of L-WNK1 by dietary K+

Abstract: Flow-induced K+ secretion in the aldosterone-sensitive distal nephron is mediated by high-conductance Ca2+-activated K+ (BK) channels. Familial hyperkalemic hypertension (pseudohypoaldosteronism type II) is an inherited form of hypertension with decreased K+ secretion and increased Na+ reabsorption. This disorder is linked to mutations in genes encoding with-no-lysine kinase 1 (WNK1), WNK4, and Kelch-like 3/Cullin 3, two components of an E3 ubiquitin ligase complex that degrades WNKs. We examined whether the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 112 publications
1
17
0
Order By: Relevance
“…These results are consistent with the notion that WNK4 enhances the routing of BK channels to lysosomes in a ubiquitin-dependent manner (260) that is also dependent on activation of MAPKs (250). In contrast to its effect on ROMK, L-WNK1 significantly increases BK␣ whole cell and functional expression in HEK293 cells (114,224). L-WNK1 expression reduced ERK phosphorylation, whereas knockdown of WNK1 increased the ubiquitination of BK␣, effects that are opposite to the effects seen with WNK4 (114).…”
Section: 41 230)supporting
confidence: 89%
See 2 more Smart Citations
“…These results are consistent with the notion that WNK4 enhances the routing of BK channels to lysosomes in a ubiquitin-dependent manner (260) that is also dependent on activation of MAPKs (250). In contrast to its effect on ROMK, L-WNK1 significantly increases BK␣ whole cell and functional expression in HEK293 cells (114,224). L-WNK1 expression reduced ERK phosphorylation, whereas knockdown of WNK1 increased the ubiquitination of BK␣, effects that are opposite to the effects seen with WNK4 (114).…”
Section: 41 230)supporting
confidence: 89%
“…L-WNK1 expression reduced ERK phosphorylation, whereas knockdown of WNK1 increased the ubiquitination of BK␣, effects that are opposite to the effects seen with WNK4 (114). Surprisingly, both KS-WNK1 and kinase dead L-WNK1 increased BK␣ whole cell expression in HEK293 cells, suggesting that WNK1 kinase activity is not required to enhance BK␣ expression (224).…”
Section: 41 230)mentioning
confidence: 85%
See 1 more Smart Citation
“…BK Channels Are Increased in Principal Cells of the CNT/CD in Nedd4L Pax8/LC1 Mice Because WNK1 is a positive regulator of BK channels, 42,43 we also assessed BK expression by Western blot, and found that the channel-forming BKa and BKb1 (but not BKb4) subunits were increased in total kidney extracts ( Figure 7, A and B). Immunostaining showed that BKa subunits were detectable in the CNT/CD despite active hypokalemia, and their expression was enhanced by about 30% in the CNT/CCD of Nedd4L Pax8/LC1 mice ( Figure 7, C and D).…”
Section: Nedd4l Pax8/lc1 Mice Display a Defect In K + Retention Undermentioning
confidence: 99%
“…thus, independent of ENaC, presumably reflecting the recruitment of a non-PC-mediated pathway for K + secretion into the urine (30); (c) dietary K + loading of rabbits leads to an increase in ICs of immunodetectable apical BKα and the long isoform of with-no-lysine kinase 1 (L-WNK1), a kinase that increases BKα abundance and functional channel expression in heterologous expression systems (31,32); (d) the apical membrane of the IC is depolarized relative to that of the PC (26,33,34), suggesting that there exists a favorable driving force for K + efflux across this membrane; and (e) increases in tubular fluid flow rate lead to increases in the intracellular Ca 2+ concentration ([Ca 2+ ] i ) in both ICs and PCs (35)(36)(37), and only a modest increase in [Ca 2+ ] i is necessary to open BK channels (26).…”
Section: Introductionmentioning
confidence: 99%